Off-label use of rituximab for systemic lupus erythematosus in Europe. Issue 1 (6th September 2016) - Rydén-Aulin, Monica; Boumpas, Dimitrios; Bultink, Irene; Callejas Rubio, Jose Luis; Caminal-Montero, Luis; Castro, Antoni; Colodro Ruiz, Agustín; Doria, Andrea; Dörner, Thomas; Gonzalez-Echavarri, Cristina; Gremese, Elisa; Houssiau, Frederic A; et al.
Abstract : Objectives: Rituximab (RTX) is a biological treatment used off-label in patients with systemic lupus erythematosus (SLE). This survey aimed to investigate the off-label use of RTX in Europe and compare the characteristics of patients receiving RTX with those receiving conventional therapy. Methods: Data on patients with SLE receiving RTX were taken from the International Registry for Biologics in SLE retrospective registry and complemented with data on patients with SLE treated with conventional therapy. For nationwide estimates of RTX use in patients with SLE, investigators were asked to provide data through case report forms (CRFs). Countries for which no data were submitted through CRFs, published literature and/or personal communication were used, and for European countries where no data were available, estimates were made on the assumption of similarities with neighbouring countries. Results: The estimated off-label use of RTX in Europe was 0.5%–1.5% of all patients with SLE. In comparison with patients with SLE on conventional therapy, patients treated with RTX had longer disease duration, higher disease activity and were more often treated with immunosuppressives. The most frequent organ manifestations for which either RTX or conventional therapy was initiated were lupus nephritis followed by musculoskeletal and haematological. The reason for treatment was, besides disease control, corticosteroid-sparing for patients treated with conventional therapy. Conclusions: RTX use for SLE in Europe is restrictive and appears to be used as a last resort in patients for whom other reasonable options have been exhausted.